Faktor Pemicu Pencemaran Kualitas Air Sungai Deli Kota Medan - Agustina Rahayu Sianturi; Putri Anatasya Simanjuntak; Aprilia Zaeni Rapiah; Meilinda Suriani Harefa (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research refers to observations of research locations and also literature reviews through journals and books. The data attached by the author is the result of a combination of qualitative research methods and quantitative research methods, qualitative methods are used to observe and make direct observations to the research location, while quantitative research methods to find the data needed by the author. Water pollution in the Deli River refers to a situation where the quality of river water decreases due to the intrusion of pollutants from various sources. The Deli River, like many other rivers, can be polluted by various types of waste from industrial, domestic, agricultural and other human activities, thus exceeding the river's natural recovery capacity. This research was conducted to examine social problems that occur in the community.